Optimal Reasoning of Goals in Agent-Oriented Systems - Muniyappa Gounder Subramanian, Chitra (Curtin University, 2017)
This thesis proposed a novel fuzzy-based approach for quantitative reasoning of goals in the i* framework for early requirements engineering. The fuzzy-based quantitative approach is extended by using an operation research technique namely optimisation. Furthermore, a novel approach based on game theory to manage requirements of a conflicting nature has been proposed. A tool has been developed to implement the proposed approaches and it was evaluated against OpenOME, an existing tool for the i* framework.